Pengaruh Minat Anggota Terhadap Perkembangan BMT UGT Sidogiri Cabang Jakarta - Mukarromah Mukarromah; Ign Oka Widana (ITB AAS INDONESIA Surakarta, 2021)
This study examines the influence of interest on the development of BMT UGT Sidogiri Jakarta Branch by using TPB (Theory of Planned Behavior) as the theoretical basis and using PLS (Partial Lease Square) as a tool to measure interest. BMT UGT stands for Baitul Mal wa Tamwil and the Integrated Joint Venture. These two things are part of the name for BMT which was founded by alumni of the Sidogiri Islamic boarding school. This study aims to examine how interest can influence the development of BMT UGT Sidogiri Jakarta Branch. Seeing that more and more people are aware of the prohibition of usury and BMT Sidogiri as one of the financial institutions based on sharia principles and free from usury. In this study, Theory of panned behavior is used as a theoretical basis to see the influence of attitudes, subjective norms and behavioral control on members' interests, so that it is from the interests of members that it can be seen how the development of BMT UGT Sidogiri Jakarta Branch. The results of the analysis show that subjective norms have the most positive and significant influence on the development of BMT UGT Sidogiri Jakarta Branch. Subjective norms are the most influential variable on members' interests because external and internal pressures will greatly influence members' behavior. Keywords: BMT development, Theory of Planned Behavior, Member interests.